Phytochemical investigations of species of semi-arid Australian plants: A neglected area of research.1*c - Kerr, Philip G. (Pharmacognosy Communications)
Approximately 80% of mainland Australia is considered to be arid or semi-arid.[1] Most of the desert flora remains unexplored. There is a wealth of anecdote from first nation Australians, with a number of books detailing Aboriginal use of plants[2-7] and papers, dealing with either single plant species or groups of species reported as being used by Australian Aboriginal people, scattered throughout the literature.[8-15] These provide a good deal of information that can be a stepping stone to investigate the medicinal potential of a large number of desert floral species.